The Use of Suffix -i and -kan in Indonesian Online Newspapers: A Corpus-Based Study - Fatin Fatin (Passage, 2015)
This research aims to analyze the use of suffix {–i} and {–kan} in Indonesian online newspapers by discovering the bases as well as grammatical meanings and functions that are shown by the use of each suffix. The researcher also attempts to analyze the differences between suffix {–i} and {–kan}. Two hundred thousand words of the articles from three Indonesian online newspapers, Kompas, Republika, Tempo, were taken for being analyzed. The data were analyzed by a corpus program AntConc. For the knowledge of suffixes, the researcher used Sneddon’s (2010) book as a guidance. The results showed that the noun bases often appear to be attached by suffix {-i} and {-kan}. It can be concluded that the use of suffix {-kan} are more common in the articles of formal documents, in this case Indonesian online newspapers, because many Indonesian bases that come from English, which mostly appear in the formal documents, can be only attached by suffix {-kan}. Keywords: AntConc, Grammatical Functions, Grammatical Meanings, Suffix {-i}, Suffix {-kan}